The Relationship Between School Climate and Student Self-efficacy: Evidence from High Schools - Aksoy, Oktay; Yirmibeş, Ahmet; Parlak, Nusret; Yirmibeş, Ahmet (Bartın Üniversitesi, 2025)
The objective of this study is to assess the school environment and the levels of self-efficacy among high school students, as well as to examine the correlation between the school environment and their views of self-efficacy. The study involved a total of 1492 high school students. The data was analyzed using MANOVA, correlation, and hierarchical regression methods. The findings suggest that students' self-efficacy judgments vary according to the sort of school they attend. Furthermore, the findings suggest that the students' impressions of their self-efficacy remained constant despite their advancing grade level. Certain sub-factors related to school climate are linked to specific sub-factors of self-efficacy, and these variables mutually predict one another. Concerning the findings, we offer recommendations about the school climate and individuals' belief in their abilities.
Keywords: Specialist Studies in Education (Other); Eğitim Üzerine Çalışmalar (Diğer)